CRITICAL ANALYSIS OF DECISION MODELING AND NATURAL LANGUAGE PROCESSING IN IN HEALTH INFORMATICS - Abeer Slman Suliman Alarinbi, Khulud Sulaiman Faraj Altuqayqi, Khulud Aied Maharb Al Gohani, Thoraia Salem Alatwei, Ohood Hassan Alamri, Alhanouf Mohammed Alhawiti, (Chelonian Research Foundation, 2022)
Informatics in health is a significant field, with decision modeling and natural language processing (NLP) playing critical roles that help improve healthcare delivery, positive patient results, and resource allocation. This paper aims to analyze the role of decision modeling and NLP in health informatics, regarding their positive and negative aspects, and to suggest possible future directions for their implementation. This summarizes a literature review, methodologies, and empirical research that indicate the advantages and disadvantages of NPV (net present value). It is a crucial topic since it is the basis on which the interplay between the decision-making model and the NLP systems in health care can be brought to life and, consequently, can be used to create innovations and treat new healthcare problems. One for the better here is the proposed steps for further development. They may vary, including proposing specific solutions to adopting advanced models, NLP technology, and big data in health informatics. Keywords: health information technology, models, natural language processing, health care delivery,